Pro ASP.NET Core 3 : Develop Cloud-Ready Web Applications Using MVC, Blazor, and Razor Pages - Freeman, Adam (APress, Imprint Apress., 2020)
Now in its 8th edition, Pro ASP.NET Core has been thoroughly updated for ASP.NET Core 3. This comprehensive, full-color guide is the only book you need to learn ASP.NET Core development! Professional developers get ready to produce leaner applications for the ASP.NET Core platform. This edition puts ASP.NET Core 3 into context, and takes a deep dive into the tools and techniques required to build modern, extensible web applications. New features and capabilities such as MVC 3, Razor Pages, Blazor Server, and Blazor WebAssembly are covered, along with demonstrations of how they can be applied in practice. Following the same popular format and style found in previous editions, author Adam Freeman explains how to get the most out of ASP.NET Core 3. Starting with the nuts-and-bolts topics, he teaches readers about middleware components, built-in services, request model binding, and more. Moving along, he introduces increasingly more complex topics and advanced features, including endpoint routing and dependency injection. Written for professionals wanting to incorporate the latest functionality of ASP.NET Core 3 into their projects, this book also serves as a complete reference on ASP.NET Core. Beginners with some background in Microsoft web development will also greatly benefit from the in-depth coverage provided throughout. What You Will Learn: Build a solid foundation and skill set for working with the entire ASP.NET Core platform Apply ASP.NET Core 3 features in your developer environment; plentiful reusable templates See how to create RESTful web services, web applications, and client-side applications Leverage existing knowledge to efficiently get up and running with new programming models Adam Freeman is an experienced IT professional who has held senior positions in a range of companies, most recently serving as chief technology officer and chief operating officer of a global bank. Now retired, he spends his time writing and long-distance running. "The Rolls-R oyce of ASP.NET books, (or if youre American, the Cadillac). Very thorough!" Les Jackson, MCSD, DotNet Playbook "The authors instruction is direct, easy to understand and supplemented with clear code examples... Whether you are a beginner learning ASP.NET Core 3.1 app development, or an experienced professional ready to master advanced concepts, I consider this book a 'must have' for you!" Jeremy Likness, Senior Program Manager, Microsoft "...the best single resource for teaching MVC web apps using ASP.NET. " Charles Carter, MSCS, MSwE, JD, Cloud Application Development Instructor, Microsoft Software and Systems Academy.- Resumé vydavatel